Longitudinal Diffusion Tensor Imaging Resembles Patterns of Pathology Progression in Behavioral Variant Frontotemporal Dementia (bvFTD) - Kassubek, Jan; Müller, Hans-Peter; Del Tredici, Kelly; Hornberger, Michael; Schroeter, Matthias L.; Müller, Karsten; Anderl-Straub, Sarah; Uttner, Ingo; Grossman, Murray; Braak, Heiko; Hodges, John R.; Piguet, Olivier; et al. (Frontiers in Aging Neuroscience, 2018)
Objective: Recently, the characteristic longitudinal distribution pattern of the underlying phosphorylated TDP-43 (pTDP-43) pathology in the behavioral variant of frontotemporal dementia (bvFTD) excluding Pick’s disease (PiD) across specific brain regions was described. The aim of the present study was to investigate whether in vivo investigations of bvFTD patients by use of diffusion tensor imaging (DTI) were consistent with these proposed patterns of progression. Methods: Sixty-two bvFTD patients and 47 controls underwent DTI in a multicenter study design. Of these, 49 bvFTD patients and 34 controls had a follow-up scan after approximately 12 months. Cross-sectional and longitudinal alterations were assessed by a two-fold analysis, i.e., voxelwise comparison of fractional anisotropy (FA) maps and a tract of interest-based (TOI) approach, which identifies tract structures that could be assigned to brain regions associated with disease progression. Results: Whole brain-based spatial statistics showed white matter alterations predominantly in the frontal lobes cross-sectionally and longitudinally. The TOIs of bvFTD neuroimaging stages 1 and 2 (uncinate fascicle – bvFTD pattern I; corticostriatal pathway – bvFTD pattern II) showed highly significant differences between bvFTD patients and controls. The corticospinal tract-associated TOI (bvFTD pattern III) did not differ between groups, whereas the differences in the optic radiation (bvFTD pattern IV) reached significance. The findings in the corticospinal tract were due to a ‘dichotomous’ behavior of FA changes there. Conclusion: Longitudinal TOI analysis demonstrated a pattern of white matter pathways alterations consistent with patterns of pTDP-43 pathology.